Center-Pivot-Irrigated Dry-Edible Bean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 2000)
This publication projects a budget that reflects expected income and costs based on typical center-pivot-irrigated dry-edible bean production practices in western Kansas.
MF998_2000_10
Keywords: MF999; Economics; Crops; MF